High pressure effects on the excitation spectra and dipole properties of Li, Be+, and B2+ atoms under confinement - Martínez-Flores, César; Cabrera-Trujillo, Remigio (Matter and radiation at extremes, 2020)
Properties of atoms and molecules undergo significant changes when subjected to spatial confinement. We study the excitation spectra of lithium-like atoms in the initial 1s22s electronic configuration when confined by an impenetrable spherical cavity. We implement Slater’s X-α method in Hartree-Fock theory to obtain the excitation spectrum. We verify that as the cavity size decreases, the total, 2s, 2p, and higher excited energy levels increase. Furthermore, we confirm the existence of crossing points between ns-np states for low values of the confinement radius such that the ns → np dipole transition becomes zero at that critical pressure. The crossing points of the s-p states imply that instead of photon absorption, one observes photon emission for cavities with radius smaller than the critical radius. Hence, the dipole oscillator strength associated with the 2s → 2p transition becomes negative, and for higher pressures, the 2s → 3p dipole oscillator strength transition becomes larger than unity. We validate the completeness of the spectrum by calculating the Thomas-Reiche-Kuhn sum rule, as well as the static dipole polarizability and mean excitation energy of lithium-like atoms. We find that the static dipole polarizability decreases and exhibits a sudden change at the critical pressure for the absorption-to-emission transition. The mean excitation energy increases as the pressure rises. However, as a consequence of the critical transition from absorption to emission, the mean excitation energy becomes undetermined for higher pressures, with implications for material damage under extreme conditions. For unconfined systems, our results show good to excellent agreement with data found in the literature.
Im Titel sind "+" und "2+" hochgestellt
Gesehen am 01.09.2020